Development of Interactive LKPD Based on Augmented Reality Media on Chemical Equilibrium Material - Khairunisa, Dira; Juwita, Intan; Putra, Adhitya Shahrian; Egya, Juwita Marine; fina, Al; Bangun, Kurnia Wati Br; Muchtar, Zainuddin (Jurnal Pendidikan dan Pembelajaran Kimia, 2024)
The development of technology in the world of education is a demand for the curriculum, so currently technology is developing, namely Augmented Reality, which allows its use to interact in a real way with the system. The application of Augmented Reality can be a solution to educational problems that require the application of science and technology in every subject, especially chemistry in chemical equilibrium material. Augmented Reality-based LKPD was developed based on validation results, teacher and student responses. The development method used is the research and development (R&D) method with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model. The data collection techniques used were teacher interviews, analysis of student needs, media and material validation sheets and student response questionnaires. Based on validation carried out on interactive LKPD based on Augmented Reality on chemical equilibrium material, the level of validation by media expert validators was 95% with the criteria "very feasible". And a response test was carried out on students, obtaining a percentage of 76% with the "interesting" criteria. So it can be concluded that overall the interactive LKPD product based on augmented reality media on chemical equilibrium material that has been developed is interesting for students to study for use in the learning process, especially on chemical equilibrium material.Keywords: LKPD, Augmented Reality, Chemical EquilibriumDOI: 10.23960/jppk.v13i3.32181